Strategic priorities of educational activity in the single world educational space (Pedagogy of Higher and Secondary Education, 2021)
The article considers the search of invariant general ideas for the choice of strategic priorities of educational acticity in single outer educational space, the way to make the life intelligent, and to help in personality formation.
Keywords: continuous education; education of adults; educational systems; studies during life; outer educational space